Home Care Improves Knowledge, Attitude, Practice and Blood Pressure Control in Hypertensive Patients: Exploring the Expanded Role of Community Pharmacists - Ramadaniati, Hesty Utami; Anggriani, Yusi; Saragi, Sahat; Yazid, Ricky Chaerul (JSFK (Jurnal Sains Farmasi & Klinis), 2020)
Hypertension remains a leading cause of morbidity and mortality.This study aimed to evaluate the impact of community pharmacists-provided home care on knowledge, attitude, practice (KAP) and blood pressure (BP) control of hypertensive patients. A quasi-experimental study was conducted in two pharmacies in Banten involving hypertensive patients regularly refilling prescriptions. Patients in Pharmacy A were assigned in the intervention group (IG), whilst those in Pharmacy B in the control group (CG). IG received home care in addition to standard care. Questionnaires to assess KAP were distributed at the initiation and end of the study. BP was measured monthly. A total of 110 patients (60 in IG vs 50 in CG) were enrolled. At baseline there was no significant difference in demographic and clinical characteristics. Post-intervention, proportion of patients with ‘good’ knowledge was considerably higher in IG (100%) vs 2.0% in CG, IG demonstrated ‘very ideal’ attitude compared to ‘less ideal’ in CG, IG performed ‘good’ practice as opposed to ‘fair’ practice in CG. The decrease of systolic BP in IG was significantly greater (14.8 mmHg) vs 1.8 mmHg in CG. In conclusion, expanded role of community pharmacists in providing home care improves KAP and BP control in hypertensive patients.